2011
DOI: 10.5352/jls.2011.21.8.1183
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Environmental Factors on the Growth of Microcystis aeruginosa (Cyanobacteria) in Agricultural Reservoirs

Abstract: The present study is aimed at examining the effects of the physico-chemical environmental factors of water systems on water bloom at Homin and Gagok reservoirs in Pungcheon-Myeon, Andong, Gyeongsangbuk-do. The mean water temperature and the contents of chlorophyll-a, total-nitrogen, total-phosphorus and phosphate-phosphorus were higher at the Gagok reservoir. On the other hand, the pH mean value was higher at the Homin reservoir. The mean value of microelements (Na, K, Mg, Fe, Si) was higher at the Gagok reser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…It has been suggested that HPND of mitten crabs might be occur in the high pH of water, massive aquatic plants, high abundant of cyanbacteria, fertilizers, crab feeding and hypoxia [2]. Ding et al [3] reported that infection of microsporidian Hepatospora eriocheir was associated with HPND, but animal regression test was not carried out.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that HPND of mitten crabs might be occur in the high pH of water, massive aquatic plants, high abundant of cyanbacteria, fertilizers, crab feeding and hypoxia [2]. Ding et al [3] reported that infection of microsporidian Hepatospora eriocheir was associated with HPND, but animal regression test was not carried out.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast with other Korean eutrophic reservoirs with dominant Microcystis spp. (Kwon et al, ), dominant Cyanophyta species varied between seasons, and three species had similar relative densities of 25.0–98.5%. Moreover, Anabaena sp.…”
Section: Resultsmentioning
confidence: 96%